Generation and enhancement of SRS sub-nanosecond pulses in self-focusing organic substances - Isaenko, O.Iu.; Ivanisik, A.I.; Korotkov, P.A.; Ponezha, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The possibility to use self-focusing organic substances in order to create highly efficient transformers of laser radiation based on stimulated Raman scattering has been researched. The proposed and implemented optical schemes are suitable for generation of seed sub-nanosecond Stokes pulses, due to dynamics of self-focusing, and the compression of giant pulses of multimode laser with high (>20) increase in the intensity at a shifted frequency